The breakers [compact disc, unabridged] - Muller, Marcia (Muller, Marcia. Sharon McCone mysteries, 2018)
The disappearance of a young recovering addict in southwest San Francisco leads private investigator Sharon McCone to the site of a Prohibition-era nightclub, where she discovers a ghastly chamber of horrors.